The Intention to Use Digital Payment for Sellers of Rawa Belong Flower Market in Jakarta - Tamara, Dewi (Community Development Journal, 2025)
This study aimed to asess the intention to use of digital payments among sellers in Flower Market Rawa Belong. The digital payments are including electronic wallets, mobile banking or digital banking. This study use the original Technology Acceptance Model framework to investigate and analyze the usage plan among the micro, small and medium enterprise. This study applies all the core concepts of TAM which consist of perceived usefulness, perceived ease of use, attitude, behavioral intention and actual system use (Davis, 1989). The quantitative method was adopted, in which the target population of 500 flower sellers, was conveniently selected samples, 250 flowers sellers. A structured questionnaire was developed using indicators instrument. The data is analyzed with descriptive statistic and presented in table of frequency. The findings shows first three indicators (perceived usefulness, perceived ease of use and attitude) are positive, however behavioral intention and actual system use shows different trends. Additional features like promotions, cashback offers, and integration with other platforms also made the sellers more interested in using it. The drawback from the seller is the transaction is not real time, unable to use the cash directly, the difficulties to transfer the funds to other asset quickly and they have to provide more than one application because the customers have different apps. However, the sellers have the intention to learn more about the digital payment because it improves efficiency and convenience, safety and security. The most used digital payment applications consist of OVO, GoPay, and Flip, with mobile banking provider is BCA and BRI. The findings suggest that these technologies are well aligned with governmental initiatives aimed at advancing financial inclusion and fostering the transition toward a cashless society. Furthermore, the results offer practical implications for digital payment providers, underscoring the importance of enhancing user interface design, ensuring system reliability, and developing innovative features to strengthen their competitive position in the market.